Evolution of human language: duetting as part of prosociality and cognition - Kaplan, Gisela (Frontiers in Ecology and Evolution, 2023)
Human language evolution has been of undiminished interest for generations and various origins of human language have been proposed. This paper will engage with two aspects of the debate, namely the gestural versus the turn-taking/duetting models. Research in our laboratory has included vocalisations in marmosets, gibbons, orang-utans and wild dogs as well as in avian species. My research led me to the hypothesis that not only gestural communication, but mimicry expressed in dance/music and vocals (song and calls of which duets may be indicative), preceded human speech evolution. These facets are explored in the context of synchronicity, prosociality and cognition. Notwithstanding the physiological and postural adaptations needed to alter the vocal apparatus to enable speech, we now know that in neocortical evolution, neuronal circuits arose independently of lamination across vertebrates. Indeed, at the microcircuitry level of the brain, it has been found that over time of evolution from birds to humans, i.e. the best part of 300 million years, relatively few novel features were introduced in the forebrain. It is argued that gestural origins theories have to take note of Darwin’s theory of a musical ‘protolanguage’ (in The Descent of Man, 1871). Hence this paper takes a multidisciplinary/multimodal approach including dance and music to elaborate on duetting and on human language evolution. 1 Darwin C. 1871. The Descent of Man and Selection in Relation to Sex. John Murray, London.